2013
DOI: 10.1242/jcs.126839
|View full text |Cite
|
Sign up to set email alerts
|

In vivo interactions of TTDA mutant proteins within TFIIH

Abstract: SummaryTrichothiodystrophy group A (TTD-A) patients carry a mutation in the transcription factor II H (TFIIH) subunit TTDA. Using a novel in vivo tripartite split-GFP system, we show that TTDA interacts with the TFIIH subunit p52 and the p52-TTDA-GFP product is incorporated into TFIIH. p52-TTDA-GFP is able to bind DNA and is recruited to UV-damaged DNA. Furthermore, we show that two patient-mutated TTDA proteins can interact with p52, are able to bind to the DNA and can localize to damaged DNA. Our findings gi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 23 publications
0
22
0
Order By: Relevance
“…As we have not performed TTDA protein analysis, we cannot verify the formation of TTDA proteins truncated by 24% and there is another possibility of no TTDA expression by nonsense‐mediated TTDA mRNA decay. However, each of the abnormalities may be related to the various symptoms of TTD noted in the present patient because mutant p8 proteins (L21P and R56X) have been reported to not interact with p52, resulting in a reduced quantity of TFIIH and a mutant p8 protein (E55X) similar to R56X bearing p8 protein is thought to not function normally.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…As we have not performed TTDA protein analysis, we cannot verify the formation of TTDA proteins truncated by 24% and there is another possibility of no TTDA expression by nonsense‐mediated TTDA mRNA decay. However, each of the abnormalities may be related to the various symptoms of TTD noted in the present patient because mutant p8 proteins (L21P and R56X) have been reported to not interact with p52, resulting in a reduced quantity of TFIIH and a mutant p8 protein (E55X) similar to R56X bearing p8 protein is thought to not function normally.…”
Section: Discussionmentioning
confidence: 83%
“…The photosensitive type of TTD is mutated in XPB , XPD and GTF2H5 (a gene for TTDA/p8), three of the units of TFIIH, which functions as a transcription factor and recruits to the site of UV‐induced DNA damage, resulting in subsequent steps of NER: opening, incision and excision. An 8‐kDa protein is important for maintaining UV irradiation resistance and is essential for NER and transcription …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These data seem to be against the proposed role for p8 in maintaining TFIIH stability and in contrast to the observation of lower levels of the TFIIH subunits in human cells derived from patients, who suffer from TTD-A. However, the p8 mutations described in these patients seem not to be null, and it has recently been reported that they still may interact with TFIIH [14,34]. Thus, it is possible that these mutations may generate p8 proteins that have some toxic effect when they are assembled into TFIIH, generating instability in the complex.…”
Section: Discussionmentioning
confidence: 86%
“…Overexpressing TTDA in a DNA repair deficient human XP-D cells [22] or in a p52 Drosophila melanogaster mutant (Dmp52, which exhibits TTD and cancer-like phenotypes in the fly [23]), partly restored TFIIH levels and/or NER defects. Finally, a novel tripartite split-GFP system confirmed binding of TTDA to p52 in living human cells [24].…”
Section: Characterization Of Ttdamentioning
confidence: 81%